Internal Migration Data Around the World: Assessing Contemporary Practice. Issue 1 (12th March 2014) - Bell, Martin; Charles‐Edwards, Elin; Kupiszewska, Dorota; Kupiszewski, Marek; Stillwell, John; Zhu, Yu
Abstract Compared with other demographic processes, little attention has been given to the way levels and patterns of internal migration vary around the world. This can be traced in part to the absence of any central repository of internal migration data, but it also reflects widespread variation in the ways migration is measured. If robust, reliable comparisons between countries are to be made, a clear understanding of the available data is an essential pre‐requisite. This paper reports results from the Internal Migration Around the GlobE project, which established an inventory of internal migration data collections for the 193 UN member States, identifying, inter alia, the types of data collected, the intervals over which it is measured and the spatial frameworks employed. Results reveal substantial diversity in data collection practice. We assess the strengths, limitations, and utility of the six principle ways migration is measured and examine their capacity to address key questions and issues in the field. We also identify avenues for harmonisation and conclude with recommendations which aim to facilitate cross‐national comparisons. Copyright © 2014 John Wiley & Sons, Ltd.